Accessibility and active offer : health care and social services in linguistic minority communities - Drolet, Marie, 1957-; Bouchard, Pier, 1956-; Savard, Jacinthe; Bourhis, Richard Y. (Health and society (University of Ottawa Press), 2017)
"This edited volume examines language issues within the active offer of health and social services in francophone and anglophone minority communities. This multidisciplinary collective work is the first to unite researches in health, social work, sociology, political science, public administration, law and education, in order to gain more thorough knowledge of linguistic issues in health and social services, as well as of active offer in French-language services."--